Putting Voluntariness back into Automatism - Yeo, Stanley (Victoria University of Wellington Law Review, 2001)
This article challenges the common law principles governing the concept of involuntariness and its subset, automatism. It argues that the courts have misconceived the concept as having to do with unconsciousness and its derivatives, deliberation and intention. In their place, involuntariness should be defined in terms of lack of control in the sense of a total inability to contain one's actions. Such a definition will do much to clarify the confusing state of the current law, especially in relation to cases of insane automatism.